HAK DAN KEWAJIBAN GURU DALAM PERSPEKTIF FIQH PENDIDIKAN ISLAM - Ansori, M. ZAKARIYA AL; Chanifudin (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Univesitas Muhammadiyah Bengkulu, 2025)
Teachers hold a strategic position in Islamic education, not only as transmitters of knowledge but also as shapers of students’ morals and character. From the perspective of Islamic educational fiqh, the relationship between teachers and students is not merely pedagogical but also encompasses legal, moral, and spiritual dimensions. This article aims to examine teachers’ rights and obligations from the perspective of Islamic educational fiqh and their relevance to contemporary educational practice. This study employs a library research method by analyzing classical fiqh sources, the Qur’an, hadith, and contemporary Islamic education literature. The findings indicate that Islamic educational fiqh emphasizes a balance between the fulfillment of teachers’ rights, both material and non-material, and the implementation of teachers’ obligations, which include professional, moral, and spiritual aspects. This balance constitutes a fundamental principle in creating an educational system that is just, dignified, and oriented toward the formation of morally upright individuals. Therefore, an understanding of Islamic educational fiqh regarding teachers’ rights and obligations can serve as a normative foundation for strengthening teachers’ professionalism and protection in the modern era. Keywords: teachers’ rights, teachers’ obligations, Islamic educational fiqh, Islamic education